Charge-Pump Circuit in 65nm CMOS for Neural Stimulation on Deep-Brain Stimulation - Nordi, Tiago Mateus (2021)
Deep-Brain Stimulation (DBS) is an emerging area to improve the life of patients with brain deceases and one with the most dynamic research towards implantable devices. This paper presents an electronic circuit to generate mild current pulses for application on Deep-Brain Stimulation (DBS). This circuit can generate current pulses with arbitrary shapes in the range of-514μA to +514μA, with a variable frequency up to at least 130Hz, and minimum pulse duration of 90μs. The simulations showed a power consumption of 1.7mW for currents with symmetric shapes and 1.2V. This circuit was designed in a low-power TSMC 65nm CMOS process, targeting implantable devices.